Free Amino Acid Content in Human Milk Is Associated with Infant Gender and Weight Gain during the First Four Months of Lactation - Manuel E. Baldeón; Federico Zertuche; Nancy Flores; Marco Fornasini (MDPI AG, 2019)
Background: There is a growing interest regarding the physiological role of free amino acids (FAA) present in human milk (HM). Recent studies show FAA in HM could be influenced by infants’ gender and could have an important role in their growth and development. We studied the concentrations of FAA in HM and potential associations with infants’ gender and their patterns of growth in a cohort of Ecuadorian women. Methods: Human milk samples were collected after approximately eight hours of overnight fast within one week (colostrum), 2 weeks (transition milk), and 2 and/or 4 months (mature milk) after parturition. Free AA were determined by cation-exchange chromatography separation. Results: We observed significantly higher concentrations of Glu 14.40 (1.35, 27.44), Gly 1.82 (0.24, 3.4), Cys 0.36 (0.03, 0.68), and Tyr 0.24 (0.02, 0.46) in HM intended for boys. Free Glu, Gly, Cys, and Tyr concentrations increased with time of lactation. In addition, there were higher concentrations of Glu 28.62 (1.78, 55.46) and Ala 7.16 (1.26, 13.06) in HM for children that presented faster weight gain than for those with slower gain. Conclusions: The present results showed that there are differences in FAA levels in HM intended for male and fast-growing children.